2019
DOI: 10.1177/0190272519865502
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Incidental Tokenism on Private Evaluations of Stereotype-Typifying Products

Abstract: Findings from five studies demonstrate that being an incidental token member in a transient group (e.g., a woman in a group of mostly men in a store line) lowers individuals’ private evaluations of products that typify the negative stereotypes of the tokenized identity. Incidental tokenism activates negative stereotypes associated with the tokenized identity, which subsequently leads to a desire to disassociate specifically from identity-linked products that typify those stereotypes as opposed to all identity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Firstly, the cultural trait of collectivism, i.e., to work as a group rather than the emphasis on individual worth and initiative that is typical for East Asian culture, may be reflected in more group than individually prominent representation of East Asian characters (Lui and Rollock 2018). The representation of non-prominent East Asian characters in books written by White authors and illustrators may reflect diversity efforts, that is, tokenism, which may activate negative stereotypes associated with the tokenized identity (Paul et al 2020). We also found that character prominence in terms of roles and names was higher for East Asian females than males.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the cultural trait of collectivism, i.e., to work as a group rather than the emphasis on individual worth and initiative that is typical for East Asian culture, may be reflected in more group than individually prominent representation of East Asian characters (Lui and Rollock 2018). The representation of non-prominent East Asian characters in books written by White authors and illustrators may reflect diversity efforts, that is, tokenism, which may activate negative stereotypes associated with the tokenized identity (Paul et al 2020). We also found that character prominence in terms of roles and names was higher for East Asian females than males.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, mental accounting affects decision-making, meaning it is significant. Some studies show how the classification of funds differs depending on certain individual factors (Paul et al, 2017;Abeler & Marklein, 2017;Shah et al, 2015). In other words, the results of perception, appraisal, classification of finances, choice bracketing, and budgeting are the mental accounting components.…”
Section: Introductionmentioning
confidence: 99%
“…We began our exploration by focusing on two common ways that Center members support a culture of inclusion: through engaging in recruitment and mentoring of individuals from backgrounds underrepresented in engineering. Research has shown that when workplaces are not diverse (e.g., low percentages of women), there is less inclusion and more stereotyping [11] - [12]. Thus, recruiting diverse students, staff, and faculty is central to having a more inclusive culture.…”
Section: Figure 1 My Inclusion -Concepts and Survey Items Entermentioning
confidence: 99%